2005
DOI: 10.1242/jeb.01368
|View full text |Cite
|
Sign up to set email alerts
|

Symbiosis-induced adaptation to oxidative stress

Abstract: Cnidarians in symbiosis with photosynthetic protists must withstand daily hyperoxic/anoxic transitions within their host cells. Comparative studies between symbiotic (Anemonia viridis) and non-symbiotic (Actinia schmidti) sea anemones show striking differences in their response to oxidative stress. First, the basal expression of SOD is very different. Symbiotic animal cells have a higher isoform diversity (number and classes) and a higher activity than the non-symbiotic cells. Second, the symbiotic animal cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
144
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(165 citation statements)
references
References 34 publications
9
144
0
1
Order By: Relevance
“…the applied heating rate in the experimental setup. Low heating rates profoundly delay the physiological response of the coral holobiont (Middlebrook et al, 2010) and the ramping rate of 1°C day -1 used in the current study is considerably slower than in previous studies of antioxidant responses under thermal stress; these applied heating rates ranging from near-instantaneous to 4°C hour -1 (Yakovleva et al, 2004;Richier et al, 2005;Higuchi et al, 2008;Yakovleva et al, 2009;Higuchi et al, 2012;Downs et al, 2013;T. Higuchi and I. Yakovleva, personal communication).…”
Section: Tablementioning
confidence: 65%
See 2 more Smart Citations
“…the applied heating rate in the experimental setup. Low heating rates profoundly delay the physiological response of the coral holobiont (Middlebrook et al, 2010) and the ramping rate of 1°C day -1 used in the current study is considerably slower than in previous studies of antioxidant responses under thermal stress; these applied heating rates ranging from near-instantaneous to 4°C hour -1 (Yakovleva et al, 2004;Richier et al, 2005;Higuchi et al, 2008;Yakovleva et al, 2009;Higuchi et al, 2012;Downs et al, 2013;T. Higuchi and I. Yakovleva, personal communication).…”
Section: Tablementioning
confidence: 65%
“…The potential importance of host-produced hydrogen peroxide is highlighted in the current study, where host catalase activity in A. millepora at 33°C remained high until the end of the experiment, despite photosynthetic breakdown (and loss of pigment) that might be expected to limit ROS synthesis as a result of lower rates of oxygen evolution and tissue pO2 in advanced bleaching states ( Fig. 1; Nii and Muscatine, 1997;Richier et al, 2005). The presence of a high hydrogen peroxide concentration of host origin could also explain the KatG increase and APX inhibition in the symbionts of A. millepora on the final day of observation, since neither was related to changes in symbiont SOD levels.…”
Section: A Third Role For Ros and No In Coral Bleaching?mentioning
confidence: 73%
See 1 more Smart Citation
“…However, these genes are not symbiosis-specific since they are also expressed, at a lower level, in aposymbiotic animals. In the same manner, Richier et al (2005) have shown an increased superoxide dismutase (SOD) activity in symbiotic anemones compared with aposymbiotic. At a genetic level, six expressed sequence tags (ESTs) and 91 host unigenes that are differentially expressed in symbiotic state have been characterized so far (Rodriguez-Lanetty et al 2006;deBoer et al 2007).…”
Section: Fungi Ascomycotamentioning
confidence: 84%
“…However, it was found that light irradiation reduced BODIPY-SM degradation (Table 1), which should result from an alteration in membrane trafficking of the host plasma membrane along a lysosome-like pathway. Free-radical species such as ROS are generated during the light reactions of photosynthesis [39]. The use of fluorescent probes indicated that ROS were not produced at substantial levels until 3 h of light irradiation had occurred, the time at which noticeable membrane perturbation, as evidenced by labeling with Calcofluor White M2R, was observed ( Figure 3).…”
Section: Endosymbionts' Ros Generation During Light Irradiation Altermentioning
confidence: 99%